Interrelationship between variables for wave direction-dependent WEC/site-configuration pairs using the CapEx method. (1st June 2022) - Choupin, Ophelie; Henriksen, Michael; Tomlinson, Rodger
Abstract: Renewable energies are mostly compared using the Levelised Cost of Energy (LCoE). Two major components of LCoE are of interest in this study, the others being still experimental: the Annual Energy Production (AEP) and the Capital Expenditure (CapEx). Since many Wave Energy Converters (WECs), including Wavepiston, are wave direction-dependent, this research investigates the wave direction impact on the relationship between the site-configurations (site characteristics and wave climates), WEC-configurations and power, alongside AEP and CapEx. Wave climate and WEC power are expressed in 3-dimension by adding the wave direction to the common 2-dimensional space of wave height and period. Wavepiston's WEF costs are calculated using the CapEx method. Assessing the relationship between the diverse sources of AEP/CapEx variations, enabled the development of the Cost-AEP Threshold Criterion (CAEPTC) to determine the threshold where an increase in AEP becomes negligible compared to CapEx increase. CAEPTC is perhaps a better alternative to LCoE for enhanced WEC/site-configuration pairing. Based on this Criterion and the limited dataset (a challenge to most wave companies), it was apparent that the best WEC/site-configuration pairs came from configurations with the highest yearly energy production, which is not necessarily the most expensive, and for sites with lower wave energy. Highlights: Wave direction-dependent active-surge Wave Energy Converter (WEC) power analysis. Wavepiston WEC farm Capital Expenditure (CapEx) and Annual Energy Production (AEP). WEC-configuration, site characteristic, wave climate, CapEx/AEP interrelationship. Development of the Cost-AEP Threshold Criterion for WEC/site-configuration pairing. Unidirectional or high-energy wave climates appeal less WEC/site-configuration pair.